Global developments in healthcare and medical tourism - Paul, Sudip, 1984-; Kulshreshtha, Sharad Kumar, 1978- (Advances in hospitality, tourism, and the services industry book series., 2020)
"This book focuses on the current state of the global healthcare and medical tourism sector. It explores recent trends and issues impacting healthcare services, healthcare service providers, government policies and initiatives for health reforms, emerging medical tourism destinations, world class health services, health insurance, medical visas, chartered flights, cashless treatment, and technological advancements"--Provided by publisher.